Properties of dust aerosol particles transported to Portugal from the Sahara desert - Wagner, Frank (2012)
Aerosol properties of mineral particles in the far field of an African desert dust outbreak were investigated that brought Saharan dust over the Mediterranean in different layers to Portugal. The measurements were performed inside the project Desert Aerosols over Portugal (DARPO) which was linked to the Saharan Mineral Dust Experiment (SAMUM). The maximum particle mass concentration was about 150 μg m−3 and the corresponding scattering coefficient was 130 M m−1 which results in a mass scattering efficiency of 0.87 m2 g−1. The aerosol optical depth reached values up to 0.53 and the lidar ratio was between 45 and 50 in the whole dust loaded column. A comparison between particle size distributions and refractive indices derived from different instruments and models showed a general good agreement but some minor differences could also be observed. Measurements as well as calculations with a particle transport model suggest that there is a relatively higher concentration of very large particles in the upper region of the dust layer than on the surface which is likely connected with meteorological conditions at the observational site (Évora, Portugal).